Implementation of Social Character Values in Gunungsitoli State Madrasah Students - Nahar, Syamsu; Budianti, Yusnaili; Lase, Nur Alia (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
Learning that can be applied to shape the social character of students in madrasas needs an in-depth study. This is based on that learning has not been effective, some students in the class are more focused on developing cognitive abilities and minimal in forming attitudes (affective), habituation, and practice of religious teachings in life (psychomotor). This study uses qualitative methods, namely research that intends to understand phenomena about what is experienced by research subjects such as behavior, perceptions, motivations, actions, and others holistically, using data collection techniques, namely: Observation, Interview, and Documentation. The results of the implementation of learning in inculcating the values ​​of the social character of students at Madrasah Tsanawiyah Negeri Gunungsitoli City were carried out by exemplary learning methods, role-playing, giving examples, lectures, discussions, and observations. The learning method used is interesting for students to follow, and students can enthusiastically follow the learning process carried out.